2009
DOI: 10.1007/s12033-009-9222-4
|View full text |Cite
|
Sign up to set email alerts
|

Development, Characterization and Cross Species Amplification of Polymorphic Microsatellite Markers from Expressed Sequence Tags of Turmeric (Curcuma longa L.)

Abstract: Expressed sequence tags (ESTs) from turmeric (Curcuma longa L.) were used for the screening of type and frequency of Class I (hypervariable) simple sequence repeats (SSRs). A total of 231 microsatellite repeats were detected from 12,593 EST sequences of turmeric after redundancy elimination. The average density of Class I SSRs accounts to one SSR per 17.96 kb of EST. Mononucleotides were the most abundant class of microsatellite repeat in turmeric ESTs followed by trinucleotides. A robust set of 17 polymorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
3
14
0
Order By: Relevance
“…All microsatellite mar�ers amplified a maximum of three alleles per individual in all C. longa samples tested, a pattern that was also verified by Siju et al (2010). According to Ravindran et al (2007), the basic chromosome number in C. longa is x = 21; however, some aneuploid genotypes (2n = 3x = 62 or 64) have been reported (Joseph et al, 1999;Sasikumar, 2005).…”
Section: Discussionsupporting
confidence: 62%
“…All microsatellite mar�ers amplified a maximum of three alleles per individual in all C. longa samples tested, a pattern that was also verified by Siju et al (2010). According to Ravindran et al (2007), the basic chromosome number in C. longa is x = 21; however, some aneuploid genotypes (2n = 3x = 62 or 64) have been reported (Joseph et al, 1999;Sasikumar, 2005).…”
Section: Discussionsupporting
confidence: 62%
“…Out of the eighty primers designed and targeted for the amplification, twenty one polymorphic markers were identified (Tab 1). These markers generated a maximum of three alleles per genotype, tallying with the triploid status of turmeric (RAMACHANDRAN 1961, ISLAM 2004) and characteristics of SSRs reported earlier (SIGRIST et al 2010;SIJU et al 2010a, b). A total of 99 alleles were detected across 30 turmeric accessions with an average of 4.7 alleles/ locus.…”
Section: Resultsmentioning
confidence: 91%
“…Microsatellite or Simple Sequence Repeat (SSR) constitutes a robust set of molecular markers widely used for population genetic analyses, germplasm characterization, parentage analysis and marker-assisted selection in plants. So far only 17 EST-SSR (SIJU et al 2010a) and 35 genomic SSR markers (SIGRIST et al 2010, SIJU et al 2010b) have been reported in turmeric. This limited availability warrants the need to expand the existing repertoire of microsatellite markers for future studies aiming at better estimation of genetic variability for the effective conservation of the genetic resources of turmeric.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al 2010 [29], have found (AAG)n to be the most abundant repeat motif in Gossypium barbadense. Siju et al [30] also found (AAG)n to be the most abundant in turmeric accounting to 8.2%. Similarly, trimeric motifs like AGG/CCT, AGC/CGT are also fairly well represented in rice [26], maize [27], pearl millet [28], and barley [14].…”
Section: Resultsmentioning
confidence: 99%